The moderating effect of age in the relationship between E-government services and job performance - Kalsom bti Ali, Khaled Mahmoud Almashaqbeh, (Opción, 2019)
Developed countries attained e-government and used it since it achieved positive results in all public and private fields. This study aims at identifying the impact of e-government services on job performance and using age factor as moderating effect on Civil Status & Passport Department in Jordan. The present study investigated the moderation effect of age in the relationship between e-government services and job performance. Data for this study were collected from front line employees in civil status and passport department in Jordan